IMPROVING STUDENTS’ WRITING SKILL OF DESCRIPTIVE TEXT BY USING PICTURE - Tgk Lina Rahmalia (SYARIAH: Journal of Islamic Law, 2021)
The purpose of the research is to investigate whether or not pictures can improve students’ writing skill and class condition. The subject in this research is students of class VII B in SMP N 8 Banda Aceh. The method of the research is a classroom action research. This research was conducted in two cycles. Each cycle consisted of four steps: planning, action, observation and reflection. To collect the qualitative data, the writer used field notes, photograph and interview. To collect the quantitative data, the writer conducted tests. The tests were pre-test and post-tests. To analyze the qualitative data, the writer used interactive model data analysis. For the quantitative data, the writer analyzed the mean scores of the tests to compare differences between pre-test and post-test. The result of the research shows that teaching writing skill by using pictures could improve the students’ writing skill and class condition. The improvement of mean  scores showed that there was an improvement on students writing skill. The students’ mean score of pre test  is 51.15, it improves up-to 57.79 in the post-test I and up to 60.82 in the post-test II. Therefore, it could be concluded that teaching writing skill by using picture could improve the students’ writing skill.